The Sound of Art: Soundscape in Pictorial Descriptions - Maria Elisa Fina (Linguae &: Rivista di Lingue e Culture Moderne, 2020)
This study reports on an investigation of soundscape in twenty audiodelivered pictorial descriptions in English specifically designed for children, available on the official website of the Museum of Modern Art (MoMA) in Manhattan. The scripts of the pictorial descriptions were retrieved from the website’s dedicated section and annotated by means of QDA Miner Lite, a software for qualitative analysis. Drawing on van Leeuwen’s criteria for the analysis of soundscape (1999), the scripts were annotated according to a set of codes (type of speaker, speech, music, sounds, prosody) and then analysed in order to investigate how the different semiotic resources are combined to enhance children’s art experience. The results show that soundscape in the pictorial descriptions entails a complex web of significances, which challenge children’s observation skills and stimulate critical thinking. Furthermore, the use of soundscape may also result in edutainment strategies, which include gamification and dramatization.